Becoming a social worker: Chris' account - Crawford, Frances (Routledge, 2012)
Chris Murray, a young African-American male, admitted on a scholarship to a social work masters program, reflexively explores his negotiation of difference in dialogue with an Australian female social work educator twice his age. Standpoint theory and the concept of intersectionality are used to frame Chris’ experiences at a private northeast US university after achieving an undergraduate degree in his southern home state. His initial access to university came through military service. Chris was interviewed by the author as part of her international study project examining social work students’ experience of diversity in the classroom. The open-ended interview was designed to allow self-identity of difference. Chris ethnographically recounts to a stranger a subjectivity statement of who he is in relation to studying social work. Chris’ story works the hyphen between the binary of subjectivity and objectivity through the particulars of his personal history and world-view and his expectation that I as a social work educator share his seeking of social justice. His detailing of what moved him to become a social worker and contextual complexities negotiated along the way connect to wider discourses on how agency and structure play out in lived experience in seeking social justice.